Pharmacogenetic variants and risk of remdesivir‐associated liver enzyme elevations in Million Veteran Program participants hospitalized with COVID‐19 - Sony Tuteja; Zhihong Yu; Otis Wilson; Hua‐Chang Chen; Frank Wendt; Cecilia P. Chung; Shailja C. Shah; Christine M. Hunt; Ayako Suzuki; Catherine Chanfreau; Bryan R. Gorman; Jacob Joseph; et al. (Wiley, 2022)
Abstract Remdesivir is the first US Food and Drug Administration (FDA)‐approved drug for the treatment of coronavirus disease 2019 (COVID‐19). We conducted a retrospective pharmacogenetic study to examine remdesivir‐associated liver enzyme elevation among Million Veteran Program participants hospitalized with COVID‐19 between March 15, 2020, and June 30, 2021. Pharmacogene phenotypes were assigned using Stargazer. Linear regression was performed on peak log‐transformed enzyme values, stratified by population, adjusted for age, sex, baseline liver enzymes, comorbidities, and 10 population‐specific principal components. Patients on remdesivir had higher peak alanine aminotransferase (ALT) values following treatment initiation compared with patients not receiving remdesivir. Remdesivir administration was associated with a 33% and 24% higher peak ALT in non‐Hispanic White (NHW) and non‐Hispanic Black (NHB) participants (p < 0.001), respectively. In a multivariable model, NHW CYP2C19 intermediate/poor metabolizers had a 9% increased peak ALT compared with NHW normal/rapid/ultrarapid metabolizers (p = 0.015); this association was not observed in NHB participants. In summary, remdesivir‐associated ALT elevations appear to be multifactorial, and further studies are needed.